(untitled) - Campbell, John R. (Boston, 2003)
This book is aimed to serve as a text for college students and others desiring a comprehensive introduction to the biology, care, and production of domestic animals and freshwater fish raised to provide food, as well as companionship and recreation for billions of humans around the globe
Công nghệ chăn nuôi heo
Keywords: Domestic animals,Gia súc